Effect of Corn Flour Addition on the Physical and Chemical Quality of Wedelia Trilobata (L) Hitchc Weed Silage for Ruminant Livestock Feed - Sudrajat, Ajat; Syaharani, Retno Galuh; Saputra, Wahyu Candra; Rasminati, Nur; Astuti, Niken; Christi, Raden Febrianto; Ismail, Fazhana (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Research on the physical and chemical quality of weed silage with the addition of corn flour has been carried out. The research was carried out on November 30, 2024 – February 25, 2025 at the Animal Nutrition Laboratory of the Animal Husbandry Study Program, Mercu Buana Yogyakarta University and the Chem-Mix Bantul laboratory, Yogyakarta. The study used an experimental method with a complete random design (RAL) in a unidirectional pattern using 4 treatments, namely P0 (no treatment), P1 (1% corn flour), P2 (3% corn flour) and P3 (5% corn flour), then each treatment was replicated three times. In each treatment, molasses was added 0.6%, and EM4 1%. The observed variables including the physical quality of silage, namely aroma, color, mold presence, texture and pH, while the chemical quality included moisture content, crude protein content and crude fiber content. The data obtained was tabulated and analyzed by variance analysis, if there were differences, further tests were carried out with Duncan's New Multiple Range Test (DMRT). The results of the variance analysis showed no significant difference (P>0.05) in the variables of Aroma, pH, and mold presence, but indicated significant effect in the color and texture variables (P<0.05). The average moisture content of the silage in this study was P0: 54.53%; P1: 57.35%; P2: 55.79%; and P3: 55.42%, crude protein content P0: 10.27%; P1: 11.00%; P2: 9.58%; and P3: 10.05%, crude fiber content P0: 34.51%; P1: 33.69%; P2: 34.78%; and P3: 36.58%. The results of the variance analysis showed no significant difference (P>0.05) in all treatments. It can be concluded that the addition of corn flour to weed silage affects the quality of Color, and Texture, but does not affect the Aroma, Mold, pH and chemical quality. The use of 1% corn flour produced the best quality of silage.